ECONOMIC EMPOWERMENT PROGRAM FOR FAMILIES WITH FINANCIAL PLANNING IN GAMPONG BATOH, LUENG BATA SUBDISCTRICT - Elviza, Elviza; Chudri, Intan Rizkia; Ridzqy, Syifa Gebrina; Anam, Budi Safatul; Mauliansyah, Hendri (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2023)
The aim of this community service activity is to improve family skills and abilities in terms of financial management for families in Gampong Batoh, Lueng Bata subdistrict. It is expected that every family will be able to manage their household finances effectively and efficiently. Effective financial management is very important for a family, with good financial management, a prosperous household can be created. Family financial planning is carried out to optimize income and plan expenses according to the family needs. Family financial planning can also create a harmonious household. Keywords: Strengthening, Economy, Family, Financial Planning